KELAYAKAN DAN KEPRAKTISAN MODUL PRAKTIKUM TATA SURYA MENGGUNAKAN PAPER MERGE CUBE BERBASIS AUGMENTED REALITY - Maria Margareta Kwulo Kwuta; Adrianus Nasar; Ana Silfiani Rahmawati (Program Studi Pendidikan Fisika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Flores, 2022)
This study aims to determine the feasibility and practicality of the solar system practicum module using augmented reality-based paper merge cube. The type of research used is development research with the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 3 validators consisting of 1 lecturer as a media expert and 2 subject teachers as material experts, as well as 20 students. The data obtained were expert validation and a questionnaire sheet for students. Data were analyzed using descriptive statistics. The results showed that the development of the solar system practicum module using a paper merge cube based on augmented reality had a very feasible category (82.3%) for content feasibility, a decent category (79.16) for language eligibility, and a very feasible category (87.5) for the feasibility of presentation, while the practicality of the module is in the very practical category (87.2%).